La lengua Kichwa como parte de su identidad cultural en los estudiantes del tercer año de bachillerato de la unidad educativa “José María Velasco Ibarra” del cantón Guamote - Ayol Paca, Carlos Enrique (2023)
ABSTRACT: The main objective of this research was to carry out an analysis on the permanence of the Kichwa Language in the field of study of young people in the third year of Baccalaureate of the "Velasco Ibarra" Educational Unit of the Guamote canton, which serves as one more tool to the debate of the different educational and local entities within the maintenance and strengthening of their Cultural Identity. The same was carried out based on the criteria of one hundred and five students belonging to that level of studies, as well as the authorities, teachers, mothers and fathers, considered representatives of the "Velasco Ibarra" Educational Unit, where it was developed. The study based on surveys of third year high school students and interviews with the rest of the educational community. Both the survey and the interview were able to yield data that were interpreted and analyzed within the framework of the bibliographical contributions investigated on the permanence of Kichwa in educational classrooms, and the importance of their study for strengthening the cultural identity of indigenous peoples. The results of the research show that students maintain the use of Kichwa in some spaces, just as they have stopped using their native language, both in the educational space and in their community family environment, leading to the devaluation of their customs and traditions. Educational authorities, teachers, parents and the educational community in general, highlight the importance of continuing to strengthen the use of Kichwa in all educational, family and community spaces, as a way of revaluing their historical memory and cultural identity. This paper shows the aspects that are influencing the lack of use of Kichwa in the educational field, and concludes with different educational and community strategies, as well as a pedagogical proposal as a contribution to the problem raised. Keywords: Kichwa language, cultural identity, students.